2009
DOI: 10.1038/npp.2009.100
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Depression: Useful Concept, but it's Time to Revise the DSM-IV Criteria

Abstract: Stewart et al (2009) have outlined the evidence in support of the validity of the DSM-IV definition of the 'With Atypical Features' episode specifier. Although recognizing the historical significance and clinical utility of the concept of atypical depression, this article takes issue with the DSM-IV criteria. It is concluded that mood reactivity, the A or obligative criterion, is neither significantly associated with the other symptomatic criteria nor useful to diagnose atypical depression, and thus should be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0
7

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 60 publications
3
47
0
7
Order By: Relevance
“…We found that binding potentials of [ 11 C]mirtazapine in cerebral cortical regions were, in general, lower in depressed nonresponders than in healthy controls, while removal rates of [ 11 C]mirtazapine were generally higher in diencephalic regions of depressed nonresponders than in healthy controls. In keeping with the notion that depressive disorders are heterogeneous (Berlim and Turecki 2007;Parker 2000;Pae et al 2009;Thase 2009), we noted that the binding of [ 11 C]mirtazapine in brain regions of some of the depressed, antidepressant-nonresponders was well-within the normal range, whereas reduced regional binding of [ 11 C]mirtazapine was noted in other depressed subjects. A challenge for additional PET studies with [ 11 C]mirtazapine is to see whether the procedure can provide a neuromolecular-screening devise that can distinguish between neurobiologically-distinct subgroups of depressed, antidepressant-nonresponders.…”
Section: Challenges For Pet Neuroimaging Of Depressive Disorderssupporting
confidence: 89%
See 1 more Smart Citation
“…We found that binding potentials of [ 11 C]mirtazapine in cerebral cortical regions were, in general, lower in depressed nonresponders than in healthy controls, while removal rates of [ 11 C]mirtazapine were generally higher in diencephalic regions of depressed nonresponders than in healthy controls. In keeping with the notion that depressive disorders are heterogeneous (Berlim and Turecki 2007;Parker 2000;Pae et al 2009;Thase 2009), we noted that the binding of [ 11 C]mirtazapine in brain regions of some of the depressed, antidepressant-nonresponders was well-within the normal range, whereas reduced regional binding of [ 11 C]mirtazapine was noted in other depressed subjects. A challenge for additional PET studies with [ 11 C]mirtazapine is to see whether the procedure can provide a neuromolecular-screening devise that can distinguish between neurobiologically-distinct subgroups of depressed, antidepressant-nonresponders.…”
Section: Challenges For Pet Neuroimaging Of Depressive Disorderssupporting
confidence: 89%
“…This brings us to another challenge for PET neuroimaging of depressive disorders, namely that of integrating rapid advances in neuroscience into suitable positron-emitting radioligands and PET research designs. In view of the heterogeneous nature of depressive disorders (Berlim and Turecki 2007;Parker 2000;Pae et al 2009;Thase 2009), multiple molecular pathways may cause symptoms of the disease. Some of the pathways that may be causally connected to depressive disorders include genes that encode presynaptic vesicular proteins, plasma membrane receptors, intracellular signaling molecules, proteins that regulate the actin cytoskeleton, and the transcriptional regulatory machinery (Covington, III et al 2010).…”
Section: Challenges For Pet Neuroimaging Of Depressive Disordersmentioning
confidence: 99%
“…[22] Yapılan çalışmalarda atipik major depresyonu olanlarda, atipik olmayan gruba göre kadın cinsiyetin daha sık olduğu bildirilmiştir. [19,20,[23][24][25][26][27][28][29][30][31][32][33][34][35] Angst ve arkadaşlarına göre bu oran kadınlarda yaklaşık olarak 4 kat daha yüksek-tir. [11] Nörobiyolojisi Atipik depresyonun nörobiyolojisini inceleyen çalışmalar çeşitli gruplara ayrılmaktadır.…”
Section: Epidemiyolojiunclassified
“…Duygudurumda tepkiselliğin değerlendirildiği bazı çalışmalarda duygudurumda tepkiselliği atipik depresyon tanı ölçütleri olarak sadece fazlalık olmadığı, bunun yanı sıra geçerliliğin-de sorgulanabilir olduğu bildirilmiştir. [18,16,25,35] Posternak ve Zimmerman duygudurumunda tepkiselliğin olduğu hastalarda atipik depresyonun B tanı ölçütlerini karşılama oranı %31.3, duygudurumda tepkiselliğin olmadığı hastaların atipik depresyonun B tanı ölçütlerini karşılama oranı ise %32.3 olarak bulunmuştur. [16] Bu çalışmada duygudurumda tepkisellik varlığı B tanı ölçütünü karşılama oranında artış ile ilişkili olmadığı ve B tanı ölçütle-rinden herhangi biri ile bağıntılı bulunmamıştır.…”
Section: Atipik Depresyonun Tanı öLçütleriunclassified
See 1 more Smart Citation